The Importance of Agricultural Mechanics Skills Training: Implications for Agricultural Educators - Rasty, John; Anderson, Ryan (Journal of Agricultural Systems, Technology, and Management, 2025)
Current school-based agricultural educational (SBAE) programs should be focused on preparing students to enter demanding and needed occupations and/or post-secondary programs (Chumbley, et al., 2015). Agricultural mechanics is instrumental in delivering the skills students need for college and career readiness (Hubert & Leising, 2000). Through the integration of Science, Technology, Engineering, and Mathematics (STEM) into the secondary school curricula, students should be prepared with the 21st century skills needed to enter post-secondary institutions or a demanding workforce. To determine skills most important for secondary content inclusion, Laird (1994) studied agricultural education teachers to determine the depth they taught 60 agricultural mechanics skills, as well as how important those teachers perceived those skills to be in ten years. The researchers modified Laird’s instrument to include 102 skills and distributed the survey to agricultural education teachers. Results indicated that teachers perceived all 102 skills to be more important to teach in the future than they were currently being taught. Increased agricultural mechanics importance means there is increased pressure on post-secondary teacher education programs to provide necessary training.